PENGARUH EXPERIENTIAL MARKETING DAN CITRA MEREK TERHADAP LOYALITAS PELANGGAN - Imam Gozali; Bambang Riyadi; Honorata Ratnawati (Journal Of Business, Finance, and Economics (JBFE), 2023)
This study purpose to determine how the effect of experiential marketing and brand image to customer loyalty of coffee shop at Starbucks Coffee Paragon Mall Semarang. The population used in this study were all customers who had purchased coffee products at Starbucks Coffee Paragon Mall Semarang more than once. The samples used was 50 respondents, with the sampling technique used was accidental sampling. The research data source is primary data, with data collection techniques using questionnaires. The data analysis technique used is linear regression. The results of the research seen from the linear regression equation show that experiential marketing and brand image have a positive effect to customer loyalty. The results coefficient of determination show that experiential marketing and brand image can explain the variation in the customer loyalty 63.3%. The results of hypothesis testing obtained include experiential marketing having a positive and significant effect to customer loyalty, and brand image having a positive and significant effect to customer loyalty.